PROPOSTA DE MODELO PARA CONTROLE DE CUSTOS DE MANUTENÇÃO COM ENFOQUE NA APLICAÇÃO DE INDICADORES BALANCEADOS - Peres, Carlos Roberto Coelho (2007)
The continuous search for the enterprise excellency imposes the managers who the internal and external processes of the companies are managed under a boarding with strategical vision. Leaving of this principle of based enterprise management in the value creation, that if effective from initiatives, decisions and actions that create value of the company inside. The present work considers a model of management for the maintenance using a system of measurement formed for a set of performance pointers, used for evaluation of the efficiency and effectiveness of the maintenance, being overcome as estimated a strategy of control of costs of the maintenance. Its structure is based on the function of the maintenance engineering, where continuously it searchs reduction of wastefulnesses, the modification of obsolete systems and the implantation of efficient methodologies